The Effectiveness of Law Enforcement on Morality-related Crimes in Klaten, Central Java: A Comparative Study of Islamic Law and Positive Law - Rozan Avif; Luluk Qonita (Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2026)
Immorality-related crimes in Klaten Regency, Central Java, have become an increasingly complex social and legal issue, reflected in the persistence of clandestine prostitution and the involvement of various social groups, including students. This study analyzes the effectiveness of law enforcement against such crimes and examines it comparatively from the perspectives of positive law and Islamic law. Employing an empirical legal method with a comparative approach, the research is based on field observations, interviews with officials of the Civil Service Police Unit (Satpol PP), and analysis of relevant laws and regional regulations. The findings show that law enforcement has been carried out through preemptive, preventive, and repressive measures, including legal awareness programs, surveillance, joint operations, investigations, and offender rehabilitation. However, its effectiveness remains limited due to inadequate personnel, insufficient facilities, low public legal awareness, and permissive cultural attitudes toward immoral conduct. From the perspective of Islamic law, the prevention of morality-related crimes extends beyond punitive sanctions through the principles of saddu al-dharī‘ah and maqāṣid al-sharī‘ah, particularly the protection of life (ḥifẓ al-nafs), honor (ḥifẓ al-‘ird), and lineage (ḥifẓ al-nasl). The study concludes that stronger integration between positive law and Islamic legal values is necessary to enhance preventive strategies, strengthen public morality, and promote sustainable social order.